Seleção em progênies de meios-irmãos de açaizeiro com base em múltiplos caracteres para produção de frutos - Teixeira, Davi Henrique Lima (2011)
The breeding programs of assai palm (Euterpe oleracea Mart) for fruit production uses many traits in its evaluation, which difficult in somewhat the selection process of promissory plants. Knowledge of direct and indirect effects of agronomic traits on the fruit production is important, because it helps to delimit effective and selective strategies, mainly when the yield has a low heritability. Selection based in a single trait whether direct or indirect, not always is advantageous and the most efficient strategy is the simultaneous selection of all traits that contribute to the main trait. Given the above, the aims of this work were to unfold the genetic correlations between traits on the bunch and fruit production and verify the most appropriate selective strategy to simultaneous increase of production fruit components in half-sib progenies of this palm. Doing this, it was implanted in Santa Izabel do Pará an experiment with 25 half-sib progenies in the design of randomized blocks with four replications and plots of five plants. The path analyses was performed based on the genetic correlations in the level of individuals obtained from nine traits collected over the years 2005, 2006 and 2007. It was found that the total numbers of issued bunch and fruit weight per bunch are the main determinants in the assai palm´s fruit production. Moreover, the number rachilles bunch has a direct effect on fruit weight per bunch. For the selective strategy, the genetics parameter estimated and index selections were obtained on average progenies. Were applied the index of Smith and Hazel, Williams and Mulamba and Mock in three selective strategy and assigned as weights the genetic variation coefficient, the heritability and the ratio of the eigenvector associated with the original trait by the square root of eigenvalue of the first canonical variable, which contains the maximum information provided by all the characters evaluated. It was founded Williams´s index weighted by the traits heritability had the greats predicted gains in the main traits, with the selection applied to total number of bunch emitted, fruits productions per bunch and fruit weight per bunch.